Diversity of Streptococcus thermophilus Phages in a Large-Production Cheese Factory in Argentina - Quiberoni, Andrea del Lujan (2006)
Phage infections still represent a serious risk to the dairy industry, in which Streptococcus thermophilus is used in starter cultures for the manufacture of yogurt and cheese. The goal of the present study was to analyze the biodiversity of the virulent S. thermophilus phage population in one Argentinean cheese plant. Ten distinct S. thermophilus phages were isolated from cheese whey samples collected in a 2-mo survey. They were then characterized by their morphology, host range, and restriction patterns. These phages were also classi- fied within the 2 main groups of S. thermophilus phages (cos- and pac-type) using a newly adapted multiplex PCR method. Six phages were classified as cos-type phages, whereas the 4 others belonged to the pac-type group. This study illustrates the phage diversity that can be found in one factory that rotates several cultures of S. thermophilus. Limiting the number of starter cultures is likely to reduce phage biodiversity within a fermentation facility.